Determinan Harga Saham Dilihat dari Keputusan Investasi dan Kebijakan Deviden pada Perusahaan Transportasi Indonesia - Seflidiana Roza; Afni Yeni; Silvi Indriani (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
The purpose of this study is to investigate and evaluate how dividend policies and investment choices affect the stock prices of companies in the transport subsector that are listed on the Indonesia Stock Exchange (IDX) between 2021 and 2024. employing quantitative techniques in a descriptive manner. All transport businesses on the IDX are included in the study population, and 40 companies that satisfied specific requirements were selected using purposive selection procedures. Multiple linear regression analysis and traditional assumption tests are two data analysis methods used to verify the viability of the model. With a calculated t value of | 2,140 |, which is higher than the t table of | 1,975 | and a significance value of 0.034 <0.05, this study’s data processing using SPSS version 26 revealed that investment decisions have a partial positive and significant impact on stock prices. Similarly, a calculated t value of | 4,627 | > t table of | 1,975 | and a significance value of 0.000 <0.05 indicate that dividend policy has a considerable impact on stock prices. The two independent variables were shown to have a significant impact on stock prices simultaneously (F test), with a F count of 13.683 > F table 3.05. The Coefficient of Determination (R2) value was 0.148, indicating that dividend policy and investing choices account for 14.8% of stock price fluctuations, with other factors not included in this model influencing the other 85.2%.